Gravine: peculiar morphological elements of the landscape in Southern-East Italy - Doglioni, Angelo; Simeone, Vincenzo (Italian journal of engineering geology and environment, 2019)
<span data-sheets-value="[null,2,"The landscape of the area on the boundary between Basilicata and Apulia, in south-east Italy is characterized by the presence of deep narrow valleys, i.e. ravine, named gravine. These develop at the western bound of the calcareous horst named Murge highland that is part of the Cretaceous calcareous bedrock of the Apulian Foreland domain, oriented along NW-SE direction. These ravines show typical peculiarities, hich make their origin quite controversial. Traditionally, they are believed as erosive or karst valleys, cut by the action of the runoff water. However, they show an irregular state of hydrographic evolution, arising several doubts about their genesis. Here, the specific characteristics of the ravines of Matera and Ginosa are briefly analyzed and presented for emphasizing their common particular features, introducing some notes and alternative interpretations about their genesis and evolution."]" data-sheets-userformat=""2":13057,"3":"1":0,"11":0,"12":0,"15":"Arial","16":10">The landscape of the area on the boundary between Basilicata and Apulia, in south-east Italy is characterized by the presence of deep narrow valleys, i.e. ravine, named gravine. These develop at the western bound of the calcareous horst named Murge highland that is part of the Cretaceous calcareous bedrock of the Apulian Foreland domain, oriented along NW-SE direction. These ravines show typical peculiarities, hich make their origin quite controversial. Traditionally, they are believed as erosive or karst valleys, cut by the action of the runoff water. However, they show an irregular state of hydrographic evolution, arising several doubts about their genesis. Here, the specific characteristics of the ravines of Matera and Ginosa are briefly analyzed and presented for emphasizing their common particular features, introducing some notes and alternative interpretations about their genesis and evolution.